Heat stress during seed development leads to impaired physiological function and plasticity in seed oil accumulation in Camelina sativa - Nadakuduti, Satya Swathi; Laforest, Larissa C.; Tachev, Megan; Decker, Amanda N.; Egesa, Andrew Ogolla; Shirazi, Ashkon S.; Begcy, Kevin; Sarnoski, Paul J.; Buell, C. Robin (Frontiers in Plant Science, 2023)
Camelina sativa, a member of the Brassicaceae, is a low-cost, renewable oilseed crop that produces seeds up to 40% oil by weight with high potential for use in food, feed, and biofuel applications. Camelina seeds contain high levels of the fatty acids α-linolenic acid (C18:3), linoleic acid (C18:2), oleic acid (C18:1), and gondoic acid (C20:1), which have high nutritional and industrial value. The impact of climate change, especially increased frequency, and amplitude of heat waves, poses a serious threat to crop productivity. In this study, we evaluated the effect of elevated temperatures post-anthesis on the developing seeds of C. sativa and performed physiological, morphological, and chemical characterizations at 7, 14, 21, and 28 days post-anthesis (DPA), as well as at maturity. While the seed oil accumulation peaked at 21 DPA under control conditions, reaching 406mg/g dry weight, under heat stress it was only 186mg/g. Physiologically, transpiration rate (E) and internal CO2 concentration (Ci) increased between 2 to 9 days post-stress imposition and overall net photosynthesis was impaired. Seed yield, seed weight, and oil content reduced by 84.5%, 38.5% and 54.1% respectively. We demonstrate that post-anthesis heat stress causes severe yield losses and developmental plasticity in fatty acid accumulation in oilseeds.